Economic freedom and social capital: pooled mean group evidence. Issue 6 (30th March 2017) - Jackson, Jeremy J.
ABSTRACT: This article uses annual US-state-level data from 1986 to 2004 and pooled-mean group estimation based on Pesaran et al. (1999) to examine whether economic freedom influences social capital. We find economic freedom has a negative effect on our social capital measure. This result is driven by the labour market component of freedom which is indicative of the relationship between labour market freedom and Olson-type group social capital.